Standardization of Katakadi Eye Drop: An Ophthalmic Preparation (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda is science in which we study about not only Atura Chikitsa but also Swasthasya Swasthya Rakshana. In this study an eye drop which comes under Arka Kalpana of Bhaishajya Kalpana. This eye drop not only treats allergic conjunctivitis but also prevent healthy eye from allergy. Main symptoms present in allergic conjunctivitis are redness, itching, burning sensation etc. In Ayurveda we correlate cataract with Vataja Abhishyanda. This eye drop is made up of Kataka, Karpura and Madhu mentioned in Sharangdhar Samhita Uttarkhand as Netraprasadana has a great potential to prevent and treat conjunctivitis. Also in this study light towards the pharmaceutical preparation of Katakadi Eye Drop. Standard operating procedures to quality assurance of ingredients, and also adhering to Indian Pharmacopeia's specifications for the final product's safety and quality for ophthalmic preparation. Pre-clinical ocular toxicity investigations have demonstrated this formulation's safety for topical use.